Brain Injury and Neurologic Outcome in Patients Undergoing Extracorporeal Cardiopulmonary Resuscitation: A Systematic Review and Meta-Analysis. Issue 7 (July 2020) - Migdady, Ibrahim; Rice, Cory; Deshpande, Abhishek; Hernandez, Adrian V.; Price, Carrie; Whitman, Glenn J.; Geocadin, Romergryko G.; Cho, Sung-Min
Abstract : Objectives: Extracorporeal cardiopulmonary resuscitation has shown survival benefit in select patients with refractory cardiac arrest but there is insufficient data on the frequency of different types of brain injury. We aimed to systematically review the prevalence, predictors of and survival from neurologic complications in patients who have undergone extracorporeal cardiopulmonary resuscitation. Data Sources: MEDLINE (PubMed) and six other databases (EMBASE, Cochrane Library, CINAHL Plus, Web of Science, and Scopus) from inception to August 2019. Study Selection: Randomized controlled trials and observational studies in patients greater than 18 years old. Data Extraction: Two independent reviewers extracted the data. Study quality was assessed by the Cochrane Risk of Bias tool for randomized controlled trials, the Newcastle-Ottawa Scale for cohort and case-control studies, and the Murad tool for case series. Random-effects meta-analyses were used to pool data. Data Synthesis: The 78 studies included in our analysis encompassed 50, 049 patients, of which 6, 261 (12.5%) received extracorporeal cardiopulmonary resuscitation. Among extracorporeal cardiopulmonary resuscitation patients, the median age was 56 years (interquartile range, 52–59 yr), 3, 933 were male (63%), 3, 019 had out-of-hospital cardiac arrest (48%), and 2, 289 had initial shockable heart rhythm (37%). The most common etiology of cardiac arrest was acute coronary syndrome ( n = 1, 657, 50% of reported). The median extracorporeal cardiopulmonary resuscitation duration was 3.2 days (interquartile range, 2.1–4.9 d). Overall, 27% (95% CI, 0.17–0.39%) had at least one neurologic complication, 23% (95% CI, 0.14–0.32%) hypoxic-ischemic brain injury, 6% (95% CI, 0.02–0.11%) ischemic stroke, 6% (95% CI, 0.01–0.16%) seizures, and 4% (95% CI, 0.01–0.1%) intracerebral hemorrhage. Seventeen percent (95% CI, 0.12–0.23%) developed brain death. The overall survival rate after extracorporeal cardiopulmonary resuscitation was 29% (95% CI, 0.26–0.33%) and good neurologic outcome was achieved in 24% (95% CI, 0.21–0.28%). Conclusions: One in four patients developed acute brain injury after extracorporeal cardiopulmonary resuscitation and the most common type was hypoxic-ischemic brain injury. One in four extracorporeal cardiopulmonary resuscitation patients achieved good neurologic outcome. Further research on assessing predictors of extracorporeal cardiopulmonary resuscitation-associated brain injury is necessary. Abstract : Supplemental Digital Content is available in the text.